Tuning the upconversion light emission by bandgap engineering in bismuth oxide-based upconverting nanoparticles. Issue 19 (28th April 2017) - Back, M.; Trave, E.; Mazzucco, N.; Riello, P.; Benedetti, A.
Abstract : Y, Er codoped Bi2 O3 nanoparticles: chromaticity tuning of Er 3+ upconversion PL emission through host bandgap engineering mediated by Y doping control. Abstract : In the field of novel applications involving upconverting processes, the determination of new strategies for realizing emission-tunable nanomaterials is a challenge. In this work the design of Y 3+ and Er 3+ codoped bismuth oxide-based upconverting nanoparticles is presented, evidencing that the active role of the matrix allows for the emission selectivity with chromaticity control. The bandgap of the bismuth oxide-based host can be manipulated in the range of 0.65 eV, consequently leading to upconversion emission color tunability from red to yellow-greenish. The resulting fine control of the nanoparticle chromaticity through accurate host bandgap engineering reveals a novel concept for the development of a new generation of upconverting nanophosphors.